FAKTOR-FAKTOR YANG MENDASARI PENGADOPSIAN INTERNET BANKING (Studi pada PT Bank Rakyat Indonesia, Tbk) - , MAULANA WAHYU S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Internet banking is one of the banking services that use information and communication technology. The purpose of this study is to identify the effects of ease of use, trust, compatibility, third party concerns, reference group, and computer proficiency to intention to adopt Internet banking This research use purposive sampling method and data that used in this research is primary data of questionnaire. Sample of the current research is 100 people. Analysis technique that used in this research is multiple regression analysis from software SPSS 20.0. The result indicates that ease of use, trust, compatibility, third party concerns, reference group, and computer proficiency have a positive effect to intention to adopt Internet banking.